2014
DOI: 10.1126/science.1258236
|View full text |Cite
|
Sign up to set email alerts
|

An ancient defense system eliminates unfit cells from developing tissues during cell competition

Abstract: Developing tissues that contain mutant or compromised cells present risks to animal health. Accordingly, the appearance of a population of suboptimal cells in a tissue elicits cellular interactions that prevent their contribution to the adult. Here we report that this quality control process, cell competition, uses specific components of the evolutionarily ancient and conserved innate immune system to eliminate Drosophila cells perceived as unfit. We find that Toll-related receptors (TRRs) and the cytokine Spä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
275
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(290 citation statements)
references
References 47 publications
14
275
0
1
Order By: Relevance
“…Increased p53 activity was achieved by deletion of one Mdm2 allele, which conferred significant disadvantage to HSPCs cotransplanted with WT HSPCs [149]. Cellular competition is often based on induction of apoptosis in 'loser' cells [141,150,151]. Hematopoietic competition mediated by p53, however, seemed not to require killing of outcompeted cells as overexpression of Bcl-2 in the hematopoietic compartment did not influence bone marrow chimerism, and apoptosis-related genes such as Puma and Bax were not differentially regulated in the competing cell populations.…”
Section: The Role Of P53 Beyond Dna Damage Responsementioning
confidence: 99%
“…Increased p53 activity was achieved by deletion of one Mdm2 allele, which conferred significant disadvantage to HSPCs cotransplanted with WT HSPCs [149]. Cellular competition is often based on induction of apoptosis in 'loser' cells [141,150,151]. Hematopoietic competition mediated by p53, however, seemed not to require killing of outcompeted cells as overexpression of Bcl-2 in the hematopoietic compartment did not influence bone marrow chimerism, and apoptosis-related genes such as Puma and Bax were not differentially regulated in the competing cell populations.…”
Section: The Role Of P53 Beyond Dna Damage Responsementioning
confidence: 99%
“…After a genomic screen designed to discover genes required for cell competition, Rhiner et al, identified flower (fwe), a gene encoding a trans-membrane protein that also appears to be implicated in synaptic vesicle exo-and endocytosis (Yao et al, 2009). fwe generates three RNA forms, a ubiquitous one, fwe ubi , and two others, fwe Lose A and fwe Lose B , which are up regulated in loser cells during cell competition (Rhiner et al, 2010) (Meyer et al, 2014). Normally Toll and Imd activate genes encoding antimicrobial peptides, aimed to eliminate foreign pathogens like bacteria or fungi; but to eliminate loser cells this novel pathway activates the pro-apoptotic genes reaper and hid.…”
Section: Mechanisms Of Cell Competitionmentioning
confidence: 99%
“…61 It has only recently been shown that this competition relies on TOLL signaling inducing NFκB-dependent apoptosis in 'loser' cells and their subsequent engulfment by 'winner' cells. 62,63 Along this line, a natural cell competition has been described for thymic progenitor cells in the mouse. Young cells recently immigrated from bone marrow displace 'older' progenitors already residing in the thymus.…”
Section: The Apoptosis Paradox In Tumor Developmentmentioning
confidence: 99%